Assessment of serum alkaline phosphatase and calcium levels during bone fracture healing in dogs stabilized with a bone plate after being treated with an amniotic membrane loaded with platelet rich plasma (Journal of Pharmaceutical Negative Results, 2022)
Background/aim: The goal of the present study was to investigate the effects of an acellular amniotic membrane loaded with autologous platelet-rich plasma on bone healing biochemically by measuring serum factors including calcium and alkalinity in a dog model. Materials and methods: Fifteen dogs were used in the current study. The animals were divided into three groups of five dogs each. A transverse osteotomy was induced in the midshaft of the left tibia of all animals. The first group was treated with acellular amniotic membrane only by wrapping it around the fracture site. The second group was given acellular amniotic membrane and platelet-rich plasma to treat them, while the third group (the control) was left alone and not treatedWhole blood was drawn from all groups on the 0th day prior to surgery as well as on the 14th, 28th, 42nd, and 56th days following surgery. Physiological data was then reported. in order to estimate calcium and alkaline phosphatase at various phases of fracture healing. Results: the results of the present study illustrated that the serum alkaline phosphate and calcium levels increased (p≤0.01) on days 14 and 28, followed by a decreasing trend after day 28 to day 56. And their levels were higher in group AM+PRP than in other groups (39.4 ± 1.21, 15.79±0.66 respectively). When compared to the control and AM groups, the rate of formation of new bone tissue in Group AM+PRP was the fastest. It was concluded that serum alkaline phosphatase and calcium were found to be helpful biochemical indicators for evaluating bone development and contributed to proving the superiority of using the amniotic membrane loaded with platelet-rich plasma in promoting bone healing. These biochemical parameters, in conjunction with clinical and radiographic examinations, provide reliable information about the degree of bone healing.